2022
DOI: 10.2174/1574888x16666210622125309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Characteristics of Breast Milk-derived Stem Cells with the Stem Cells Derived from the Other Sources: A Comparative Review

Abstract: : Breast milk (BrM) not only supplies nutrition, but it also contains a diverse population of cells. It has been estimated that up to 6% of the cells in human milk possess the characteristics of mesenchymal stem cells (MSC). Available data also indicate that these cells are multipotent and capable of self-renewal and differentiation with other cells. In this review, we have compared different characteristics, such as CD markers, differentiation capacity, and morphology of stem cells, derived from human breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 277 publications
0
2
0
3
Order By: Relevance
“…The RNA-Seq results further proved the reliability of our research and showed that HPMSCs-Exo could be a promising therapeutic carrier. MiRNAs play an important role in the differentiation, proliferation, cytoskeleton, apoptosis, catabolism, and signaling pathway regulation of vascular endothelial cells (VECs) [40,41]. Further exploration of miRNA expression levels of HPMSCs-Exo showed that there were several miRNAs, mainly including hsa-miR-148a-3p, hsa-miR-151a-3p, and hsa-miR-423-5p.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-Seq results further proved the reliability of our research and showed that HPMSCs-Exo could be a promising therapeutic carrier. MiRNAs play an important role in the differentiation, proliferation, cytoskeleton, apoptosis, catabolism, and signaling pathway regulation of vascular endothelial cells (VECs) [40,41]. Further exploration of miRNA expression levels of HPMSCs-Exo showed that there were several miRNAs, mainly including hsa-miR-148a-3p, hsa-miR-151a-3p, and hsa-miR-423-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Стволовые клетки, выделенные из грудного молока человека, экспрессируют маркеры CD14, CD31, CD45 и CD86; идентифицирована также группа маркеров CD13, CD29, CD44, CD105, CD106, CD146, CD166 [12]. Плюрипотентные и мультипотентные стволовые клетки из образцов грудного молока демонстрируют клеточные маркеры, типичные для мезенхимальных стволовых клеток (CD90, CD105 и CD73) [10], количество которых достигает порядка 6-15% клеток [12].…”
Section: резюме _____________________________________________________...unclassified
“…Стволовые клетки, выделенные из грудного молока человека, экспрессируют маркеры CD14, CD31, CD45 и CD86; идентифицирована также группа маркеров CD13, CD29, CD44, CD105, CD106, CD146, CD166 [12]. Плюрипотентные и мультипотентные стволовые клетки из образцов грудного молока демонстрируют клеточные маркеры, типичные для мезенхимальных стволовых клеток (CD90, CD105 и CD73) [10], количество которых достигает порядка 6-15% клеток [12]. Маркеры стволовых клеток (embryonic (OCT4, SOX2, HLA-DR, NANOG, SSEA 4 и TRA-1), hematopoietic (CD33, CD34, CD45, CD117), neural (CD133, Nestin), mesenchymal (CD 29/44/73/90/271/146/106, SCA1) stem cell markers), содержащихся в молозиве и молоке кормящей женщины, характеризовались более высокой степенью экспрессии в молозиве по сравнению со свежим грудным молоком [1,4,9].…”
Section: резюме _____________________________________________________...unclassified
See 1 more Smart Citation
“…However, the number of BMSCs and their proliferation and differentiation abilities substantially decrease with aging. In recent years, researchers have attempted to search for MSCs in other tissues, such as the muscles, amniotic fluid, umbilical cord blood, and adipose tissue [ 3 ].…”
Section: Introductionmentioning
confidence: 99%